Knowledge Level of Improved Cultivation Practices of Sugarcane in Chandel District, Manipur - Khaling Sheltamdar; J. Longkumer; Mary N. Odyuo; Sashilila Ao; Sentiungshi; Benthunglo (International Journal of Economic Plants)
The study was conducted in Chandel district state of Manipur, India,under Machi CD blocks in the year 2021. Sugarcane is grown in Manipur for commercial purposes and though farmers of Chandel district is on the forefront, scope for increased production and productivity is still high yet, no major studies have been conducted in the selected district to understand the dynamics of production scenario of sugarcane till the present time of investigation. Therefore, in order to assess the knowledge level of improved cultivation practices of sugarcane, this study was conducted. Sample consists of 104 farmers selected based on Proportionate Random Sampling procedure. The study concluded that 100% (104 nos. of respondents) had knowledge related to propagation, intercultural operation, ratooning and harvesting. More than 90% of the respondents had knowledge regarding soil and varieties. More than half of the respondents had knowledge regarding land preparation, climate, weeding, seed rate and processing and an average knowledge regarding irrigation, insect and pest management and spacing. The findings revealed that the overall Knowledge Index wasfound to be medium with scores of 63.46%. The study recommends study tours to nearby model farms in the research station or framers’ fields and training programs, off farm and on farm to create awareness about the latest technology to provide first-hand information to the farmers and the extension agent or the related agricultural departments can take up front line demonstration, seminar and workshop which will help farmers to increase their farm output.